The outcast, drama in three acts (Iter, 2022)
Dante's presence in Chile is widelyevident and it is backed up by documented and concrete facts andpeoplefrom our academic environment. However, “The outcast ” drama fromVittorio di Girolamo, winner of “Experimental Drama ” prize fromP.U.C.Ch. in 1999, goes further beyond. It brings the character DanteAlighieri straight on stagey re-interpreting it freely, to the light of afaithfulness to the spirit which transcends faithfulness to historical realityof time.The daily, poetic, and mystical worid, interweave in these “Dantesque experiences ” which the author of the drama narrates andillustrates with his astonished passion and mastery.